EFFECTS OF FERTILIZER TREATMENT ON THE POLYPHENOL CONTENT IN MAIZE AND VELVETLEAF COMPETITION - Šikuljak, Danijela (Journal of Agricultural Sciences (Belgrade), 2023)
The aim of this research was to examine the effect of fertilizer treatment on the content of polyphenols in Abutilon weed (Abutilon teophrasti - AT) and corn (Zea mays - ZM), grown without use of herbicides under controlled conditions (photoperiod 12h/12h, T av. 25º/22ºC day/ night). Part of research is devoted to examining the accumulation of heavy metals in the soil after  application of fertilizers. Plants were treated with organic fertilizer - F1 (15 μl/100 ml of water) and synthetic fertilizers - F2 (1.5 ml/100 ml of water) and F3 (1.5 ml/100 ml of water). The content of total phenols, individual polyphenolic acids and antioxidant activity of plant extracts were examined, as important indicators of the plant condition and its resistance to oxidative stress. The content of total phenols was determined spectrophotometrically according to the modified Folin-Ciocalteu method. The content of individual polyphenolic acids was determined by the high-performance liquid chromatography method, while measurement of polyphenols antioxidant activity was determined by the DPPH method. It was established that in ZM, the application of organic and synthetic fertilizers, neither in monoculture nor in competition with AT plants, caused statistically significant changes in the content of polyphenolic acids. However, in AT, the use of fertilizers (organic F1, synthetic F2 and F3) led to an increase in the content of polyphenolic acids in conditions of competition vs. monoculture. The content of chlorogenic, p-coumaric and trans-ferulic acids was statistically, significantly higher in plants of AT competition vs monoculture, and the content of chlorogenic, p-coumaric and cinnamic acids was lower in plants of ZM competition vs monoculture. A statistically significant increase in the content of total polyphenols and their antioxidant activity in AT plants indicates the difficulty of removing weeds from crops, especially resistant populations. The research conducted and the results obtained confirm that weeds (Abutilon teophrasti) in competitive conditions manifest their natural competitive advantage, which is further enhanced by crop feeding. The effect of fertilizers on weed plants should be carefully considered, especially under conditions of crop cultivation without the application of herbicides.
Keywords: poliphenols, Abutilon teophrasti, Zea mays, hevy metals, competition